Effect of the crystal structure and chemical bonding on the electronic and thermal transport in Cu2MeHf3S8 (Me – Mn, Fe, Co, Ni) thiospinels - Smitiukh, Oleksandr; Soroka, Oksana; Marchuk, Oleg (Physics and Chemistry of Solid State, 2023)
Establishing the relationship between crystal structure and transport properties is an important issue that is directly connected with the applicability of functional materials. In this work, we present the analysis of the crystal structure, chemical bonding, and electronic and thermal transport properties of Cu2МеHf3S8 (Ме – Mn, Fe, Co, Ni) compounds. The increase of weighted mobility in the Mn → Fe → Со → Ni series as well as the change of the dominant scattering mechanism of charge carriers from scattering on point defects to the scattering on acoustic phonons explains the best electronic transport in Cu2NiHf3S8. Moreover, bonding inhomogeneity between the covalent δ(Co – S) and δ(Hf – S) from one side, and more ionic δ(Cu – S) interactions from the other side leads to low lattice thermal conductivity in Cu2MeHf3S8 (Me – Mn, Fe, Co, Ni) materials. The work also suggests the link between the occupation of the octahedral 16d site and the thermoelectric performance of the investigated thiospinels. Particularly, the best thermoelectric performance is observed in the case of the presence of two valence electrons in the d-level of atoms in octahedral voids, which can be essential for further enhancement of the thermoelectric performance in thiospinels.